2019
DOI: 10.1071/an17534
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fermentation and in situ rumen degradation kinetics of summer forage brassica plants

Abstract: The aim of the present study was to assess and compare the nutrient concentration, the in vitro fermentation and the in situ rumen degradation characteristics of Brassica rapa ssp. rapa L. (turnips) and Brassica napus ssp. biennis L. (forage rape). Five varieties of each species were established in three field replicates and were organised in a randomised complete-block nested design. All varieties were harvested and further analysed for chemical composition, in vitro gas-production kinetics, volatile fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…As rumen bacteria use NH 3 nitrogen and branched chain SCFAs for their growth, therefore lowering NH 3 N and branched chain SCFAs concentrations which is comparable to our study with greater MN (Roman- Garcia et al, 2016). The greater MN when supplementing FR may be due to better energy supply in the rumen because of its high DM degradation rate (Keim et al, 2019) or due to changes in microbial communities. For example, Sun et al (2015) reported that feeding FR to lambs modified bacterial communities in the rumen compared to ryegrass-fed animals.…”
Section: Rumen Functionsupporting
confidence: 80%
See 2 more Smart Citations
“…As rumen bacteria use NH 3 nitrogen and branched chain SCFAs for their growth, therefore lowering NH 3 N and branched chain SCFAs concentrations which is comparable to our study with greater MN (Roman- Garcia et al, 2016). The greater MN when supplementing FR may be due to better energy supply in the rumen because of its high DM degradation rate (Keim et al, 2019) or due to changes in microbial communities. For example, Sun et al (2015) reported that feeding FR to lambs modified bacterial communities in the rumen compared to ryegrass-fed animals.…”
Section: Rumen Functionsupporting
confidence: 80%
“…Summer turnips and FR diets contained a greater concentration of NFC compared to the control diet. According to Keim et al (2019), Barkant ST contains 82 g/kg of starch compared to 59 g/kg of starch in Spitfire FR (the cultivars used in this study) and more water soluble carbohydrates (144 v. 131 g/kg DM; specifically sucrose, glucose and fructose). These differences in type and quantity of NFC are expected to modulate rumen fermentation (Oba, 2011) and might be responsible for the greater tSCFA and butyrate in the rumen of cows (6 h after supplementation) supplemented with ST.…”
Section: Rumen Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas degradation kinetics and ruminal fermentation of summer brassica species (rape and turnip) and varieties [16] have been reported in the literature, few reports exist on the effect of winter brassica species (kales and swedes) and varieties on the in situ degradation kinetics and fermentation end products. For example, Sun et al [4] have observed that sheep fed swedes showed modified VFA profiles in their rumen fluid and lowered methane yield in contrast with those fed kales or perennial ryegrass.…”
Section: Introductionmentioning
confidence: 99%
“…Valderrama and Anrique [17] have reported DM and crude protein (CP) degradation kinetics of kale leaves; however, to the best of our knowledge, such data have not been reported for swedes. Moreover, the nutritive value of brassicas varies among species and varieties within species [3,16], and, therefore, information is still lacking about rumen fermentation and the kinetics of winter brassica species such as kales and swedes.…”
Section: Introductionmentioning
confidence: 99%